Knowledge and Attitude of Women in Reproductive Age toward Clubfoot in Cikeruh Village, Jatinangor Subâdistrict in 2014 - Fitraendi, F. M. Dicky; Fathurachman, Fathurachman; Susanto, Nugroho Harry (Althea Medical Journal, 2018)
Background: Clubfoot is a congenital anomaly which the ankle is twisted outward from the normal position. Clubfoot is the most common birth defect that can cause disability in the world. 150.000 â 200.000 babies are born with clubfoot every years. Clubfoot is a neglected disease. Immediate intervention is needed to treat the patient with Clubfoot. One of the most common barrier of the treatment is the knowledge and attitude of the society about Clubfoot. This study aimed to know the knowledge and attitude of the society especially women with reproductive age toward clubfoot in Cikeruh village Jatinangor subâdistrict in 2014.Methods: This research was conducted to 100 women with reproductive age with age interval 15â49 years old which live in Cikeruh village Jatinangor in 2014 with purposive sampling method. A questionnaire was used as instrument to collecting data which is later categorized by good, fair, and low for the knowledge and positive and negative for attitude.Results: From 100 sample women of reproductive age in Cikeruh village at 2014 who were asked about clubfoot, 39% had a good knowledge and 61% had a fair knowledge. There were 42% of respondent who had a negative attitude toward clubfoot and 58% had positive attitude.Conclusion: Majority sample women of reproductive age in Cikeruh village at 2014 have a fair knowledge about clubfoot. The ratio between positive and negative attitude toward clubfoot is almost 1:1 because of the minimal differences.Â